TARI SEKURA SEBAGAI MEDIA PELESTARI TOPENG SEKURA DARI LIWA LAMPUNG BARAT - Ahmad Susantri (Joged, 2019)
Tulisan ini membahas usaha pelestarian kebudayaan yang dimediasi oleh sebuah karya seni tari yang muncul dari kebudayaan itu sendiri. Topeng sekura sebagai produk kebudayaan dalam rangkaian acara adat Pesta Sekura Cakak Buah menjadi lebih dikenal semenjak lahirnya tari Sekura. Proses kreatif penciptaan tari Sekura tidak hanya menghasilkan sebuah karya seni namun mendapatkan posisi yang lebih ‘mulia’ yaitu sebagai media promosi yang memperkenalkan topeng sekura ke berbagai tempat yang dulunya justru tidak mungkin untuk digapai. Tulisan ini tidak hanya memaparkan keberhasilan karya tari dalam melestarikan sebuah produk kebudayaan namun bagaimana perjalanan terbentuknya kebudayaan tersebut sehingga menjadi menarik untuk dilestarikan dan menjadi alasan mengapa harus dipromosikan. This paper discusses cultural preservation efforts mediated by a dance work which arises from the culture itself. Sekura mask as a cultural product in the series of traditional evebts pf the Sekura Cakak Buah festival has become more well known since Sekura dance was born. The creation creative process of Sekura dancedoes not only produse an art work but also obtain a more ‘precious’ position as a promotional medium which acquaints the Sekura mask into various places that previously are impossible to reach. This paper does not only elaborate the succes of dance works in preserving a cultural product but also how is the process of cultural formation it self becomes attractive to be preserved and becomes the reason why it should be promoted.